P–149 Calcium ionophores as an aid to surgically retrieved sperms in male factor infertility for increasing cumulative live birth rate. (6th August 2021) - Sahu, A; Singh, S; Varghese, A C; Ashraf, R; Majiyd, N; Singh, S; Basheer, R; Ashraf, M C
Abstract: Study question: Does the addition of calcium ionophores for artificial oocyte activation(AOA) help in improving Cumulative Live Birth Rate in surgically retrieved sperms for male factor infertility? Summary answer: AOA significantly improved cumulative live birth rate in Micro-TESE (M-TESE), TESA for non- azoospermia (TESTICULAR) and Non-Obstructive Azoospermia(NOA)-TESA but not in Obstructive Azoospermia (OA)-TESA. What is known already: The main cause of Total Fertilization Failure after ICSI is thought to be due to oocyte activation deficiency (OAD) because of oocyte-related or sperm-related factors. Studies have shown that artificial oocyte activation (AOA) is helpful in these situations, but is most effective in couples who have clear sperm-related OAD. Oocyte activation, by Phospholipase- C- Zeta (PLCζ) present in the sperm, leads to series of events resulting in calcium oscillation, oocyte activation and fertilization. AOA increases the free intracellular calcium thereby mimicking physiologic cell signaling mechanisms that result in oocyte activation and fertilization. Study design, size, duration: This is a retrospective cohort study done in an academic private ART center, in which patient's records were analyzed, from January 2016 to December 2019 (total 4 years' duration) and all ICSI cycles with surgically retrieved sperms were included (n = 365). Study subjects were divided into 4 groups- M-TESE (n = 143), NOA-TESA (n = 38), OA-TESA (n = 62) and TESTICULAR (n = 92). Subdivision was done into cases if AOA was done and control were with conventional ICSI without AOA. Participants/materials, setting, methods: Method- Immediately after ICSI, in case group (AOA), all metaphase II oocytes were treated with calcium ionophore (GM508- CultActive) for 15 minutes, then thoroughly washed and incubated under standard conditions. Primary outcome measured was cumulative live birth rate(CLBR) and Secondary outcomes were fertilization rate (Fert. rate), Cleavage rate, clinical pregnancy rate (CPR) and miscarriage rate (MA). Statistical analysis was performed with Chi-square and Mann-Whitney- U test, with significance at P < 0.05. Institutional committee clearance was obtained. Main results and the role of chance: The CLBR was significantly higher with AOA- M-TESE (55.8% vs 33.3%, p- 0.008), AOA-NOA-TESA (55.55% vs 15%, p- 0.027) and AOA-TESTICULAR (62.9% vs 32.3%, p- 0.006) group. Fert. rate was significantly higher with AOA-M-TESE (81 ± 0.84 vs 64 ± 0.97, p- 0.001), AOA-NOA-TESA (86 ± 0.76 vs 64 ± 0.13, p- 0.001) and AOA-TESTICULAR (72 ± 0.12 vs 57 ± 0.11, p- 0.001). Cleavage rate, CPR also showed similar significant differences while MA was comparable. However, significant differences were not observed in any of the outcome measured in OA-TESA group between cases and controls - CBLR (51.6% vs 41.9%, p- 0.611), Fert.rate (0.77±0.14 vs 0.75±0.11, p- 0.539), CPR and MA, p- value > 0.05. It may be hypothesized that surgically retrieved sperms in cases of NOA or non- azoospermia where TESTICULAR sperms are taken have reduced or absent capacity to cause Calcium oscillations due to deficient or inadequate PLCζ or there may be some chromatin level abnormalities in these sperms, leading to lesser fertilization and lesser good quality embryos in control group in which AOA was not done. Limitations, reasons for caution: This study is retrospective in nature. Sibling oocytes were not compared. The study neither looked at obstetrics complication nor the neonatal outcomes. Further studies are required for long term impact on children born from AOA cycles. Wider implications of the findings: To our knowledge, this is the first study in the literature evaluating the efficacy of calcium ionophores for NOA (M-TESE, TESA), OA (TESA) and TESTICULAR sperms. Further research is needed for use of calcium ionophores in cases of unexplained infertility and recurrent implantation failure. Trial registration number: Not applicable